1984
DOI: 10.1103/physrevlett.53.1598
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Recombination Times in Amorphous-Silicon Doping Superlattices

Abstract: Doping superlattices, i.e., multilayer structures consisting of ultrathin (50 A ^ d =^ 400 A) tf-type, intrinsic, and /Mype layers of a-S'r.W (nipi structures), have been produced. Up to a tenfold increase in their infrared photoconductivity after band-gap illumination compared to unstructured a-Si:H is observed. The results are well described by a simple model for the carrier recombination kinetics that takes into account the spatial separation of electrons and holes due to the modulation of the band energies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(10 citation statements)
references
References 9 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…Because of the large spatial separation of charge carriers, the recombination lifetime becomes large. Porous silicon appears to show similar trends, since it is composed of small crystallites, and these introduce a fluctuation in the energy bandgap throughout the material [15]. Thus photo-excited carriers are spatially separated, which leads to an exceedingly long recombination life time.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Because of the large spatial separation of charge carriers, the recombination lifetime becomes large. Porous silicon appears to show similar trends, since it is composed of small crystallites, and these introduce a fluctuation in the energy bandgap throughout the material [15]. Thus photo-excited carriers are spatially separated, which leads to an exceedingly long recombination life time.…”
Section: Introductionmentioning
confidence: 70%
“…On the other hand, the PPC effect, traditionally observed in a-Si:H multilayers or porous Si [15], may be described by the potential barrier model for crystalline doping superlattices. According to this theory, the PPC in multilayers arises from photoinduced electron-hole pairs separated by the electric field at the p-n junction in superlattice.…”
Section: Introductionmentioning
confidence: 99%
“…A metastable excess conductance, which can be enhanced by a brief light exposure up to several orders of magnitude compared to the initial dark conductivity, has been observed in compensated aSi:H films [34][35][36][37][38][39] as well as in doping modulated multilayers of aSi:H [35,38,[40][41][42][43]. This metastable excess conductance, called persistent ph (PPC), decays slowly over several days at room temperature and disappears by annealing near 100°C in multilayered films and 200°C in compensated films [24].…”
Section: Resultsmentioning
confidence: 97%
“…They have been made on the basis of the hydrogen-induced weak Si-Si bond breaking model driven by energy released from the excess electronhole recombination. 12 This assertion can be supported by the observation of persistent photoconductivity ͑PPC͒ in the multilayer films. Liang et al 8 and Mahan and Vanecek 2 observed that there is a close correlation between hydrogen content and stability.…”
mentioning
confidence: 80%